IPTEKS BAGI MASYARAKAT (IbM) KELOMPOK PERAJIN BATIK - Tamriatin Hidayah; Agustin Hariprasetyowati; Zainollah Zainollah (STIE Mandala Jember, 2015)
Activity of IbM is a Community Service activity with the target is economically productive communities (groups of batik artisans) such as Wasp Honey (formerly name is Rangga Kencana) Rural District of Tamanan and Puri Batik Sogol in village of Dawuhan Mangli Sukowono Jember.Problems faced by the partner of IbM are in the Business Management and Problem Management Administration issues. Problem solving approach is done through the stages of observation, surveys, discussions with partners relating to the activities to be executed, the student participant debriefing, counseling and follow-up assistance. In addition it is also equipped with tools to help partners. Expected outcomes of this activity is a method and journal or National Publications. Alternative solutions are taken, including science, and technology activities in synergy with IbK through specific tenants for Entrepreneurship batik, rearrange schedules to adjust to the academic calendar, the schedule adapts to partners, and provide follow-up assistance in December. Possible to proceed further assistance, if requested by the partner or partners of the cost of Institutions Mandala College - Jember